Bacterial Translocation and Plasma Cytokines During Transcatheter and Open-Heart Aortic Valve Implantation. Issue 1 (January 2015) - Adrie, Christophe; Parlato, Marianna; Salmi, Lynda; Adib-Conquy, Minou; Bical, Olivier; Deleuze, Philippe; Fitting, Catherine; Cavaillon, Jean Marc; Monchi, Mehran
<x xml:space="preserve">Abstract</x> ABSTRACT Objective: To determine whether the good safety profile of transarterial aortic valve implantation (TAVI) is related to lower levels of systemic bacterial translocation and systemic inflammation compared with open-heart surgery. Background: Transcatheter aortic valve implantation via the transfemoral approach is increasingly used in very high-risk patients with aortic stenosis. The outcomes seem similar to those after open-heart aortic valve replacement (OHAVR). Methods: Each of 26 consecutive high-risk patients (EuroSCORE >20% for risk of operative death) who underwent TAVI (cases) was matched to the first low-risk patient treated next in our department using elective OHAVR without coronary artery bypass (control subjects). We collected severity, outcome, and echocardiography indicators before and after surgery; complications; proinflammatory cytokine levels; and markers for microbial translocation. Results: Despite greater illness severity, the TAVI patients had significantly lower vasopressor agent requirements, lower delirium rates, shorter hospital stays, and better hemodynamic findings compared with OHAVR patients. Vascular complications were more common after TAVI than after OHAVR (12, with seven requiring interventional therapy vs. 0, P = 0.006). Patients who underwent TAVI had lower blood transfusion requirements. Two TAVI patients died: one from iliac artery injury and the other from intracardiac prosthesis migration. Patients who underwent TAVI had lower plasma levels of endotoxin and bacterial peptidoglycan, as well as lower proinflammatory cytokine levels, suggesting less gastrointestinal bacterial translocation compared with OHAVR. Conclusions: Compared with OHAVR, TAVI was associated with decreases in bacterial translocation and inflammation. These differences may explain the lower delirium rate and better hemodynamic stability observed, despite the greater disease severity in TAVI patients.